Acceptance and Satisfaction of Indonesian Women Undergoing Visual Inspection with Acetic Acid (VIA) Examination Using Digital Image and The Related Factors - Madjid, Omo Abdul; Samuel Tobing; Djauhari, Jemmy Ariesandy; Fajri Harun, Siti Rafiqah (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To determine the acceptance, satisfaction, and willingness to recommend of women undergoing VIA examination with and without digital image and their related factors. Methods: This was an observational analytic study with cross sectional method. The subjects of this study were adult women undergoing VIA examination with or without digital image in Ulin Regional Hospital, Indonesia. Patients who did not fill the whole questionnaire were excluded from the study. Characteristics analyzed in the study were age, education, occupation, socioeconomic status, source of VIA information, and previous VIA experience. Outcomes analyzed in this study were acceptance, satisfaction, and willingness to recommend. Results: There were 303 subjects who were included in the study (252 with digital image and 51 without digital image). There were no risk factors of lower acceptance, satisfaction, and willingness to recommend among women undergoing VIA examination. However, the cases of women with low acceptance and satisfaction are associated with lower information of the examination. Conclusions: Digital IVA examination is a feasible alternative with acceptance, satisfaction, and recommendation rates that are the same as VIA examination without digital imaging. Keywords: cervical cancer, digital image, Femicam®, visual inspection with acetic acid examination